2016
DOI: 10.1073/pnas.1604101113
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct redox cascades cooperatively regulate chloroplast functions and sustain plant viability

Abstract: The thiol-based redox regulation system is believed to adjust chloroplast functions in response to changes in light environments. A redox cascade via the ferredoxin-thioredoxin reductase (FTR)/thioredoxin (Trx) pathway has been traditionally considered to serve as a transmitter of light signals to target enzymes. However, emerging data indicate that chloroplasts have a complex redox network composed of diverse redox-mediator proteins and target enzymes. Despite extensive research addressing this system, two fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
182
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(205 citation statements)
references
References 65 publications
11
182
2
2
Order By: Relevance
“…The results discussed above provide an explanation for the severe growth inhibition phenotype of the ntrctrxx and ntrc-trxf1f2 mutants and suggest the concerted action of both systems in the redox regulation of common targets in vivo, a notion further supported by the finding that NTRC interacts with well-established Trx targets (Nikkanen et al, 2016). Indeed, NTRC has been shown to participate in the regulation of enzymes such as AGPase (Michalska et al, 2009) and different enzymes of the pathway of tetrapyrrole synthesis (Richter et al, 2013;Pérez-Ruiz et al, 2014;Yoshida and Hisabori, 2016), which were identified previously as Trx regulated (Ballicora et al, 2000;Geigenberger et al, 2005;Ikegami et al, 2007). Here, we addressed this issue by analyzing FBPase, a well-established redox-regulated enzyme of the Calvin-Benson cycle.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 76%
See 2 more Smart Citations
“…The results discussed above provide an explanation for the severe growth inhibition phenotype of the ntrctrxx and ntrc-trxf1f2 mutants and suggest the concerted action of both systems in the redox regulation of common targets in vivo, a notion further supported by the finding that NTRC interacts with well-established Trx targets (Nikkanen et al, 2016). Indeed, NTRC has been shown to participate in the regulation of enzymes such as AGPase (Michalska et al, 2009) and different enzymes of the pathway of tetrapyrrole synthesis (Richter et al, 2013;Pérez-Ruiz et al, 2014;Yoshida and Hisabori, 2016), which were identified previously as Trx regulated (Ballicora et al, 2000;Geigenberger et al, 2005;Ikegami et al, 2007). Here, we addressed this issue by analyzing FBPase, a well-established redox-regulated enzyme of the Calvin-Benson cycle.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 76%
“…These results are surprising, since biochemical analyses have shown that FBPase is regulated by Trxs f but not by NTRC (Yoshida and Hisabori, 2016) or Trx x (Collin et al, 2003). Thus, to analyze further the role of these thiol redox systems in the regulation of FBPase, we performed in vitro assays with the purified enzymes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, a double mutant lacking FTRb and NTRC shows a lethal phenotype on soil and is only viable on Murashige and Skoog medium supplemented with Suc. Under these conditions, the mutant displays retarded growth, a weak yellow-green pigmentation, and dramatically decreased photosynthetic activity (Yoshida and Hisabori, 2016). This phenotype resembles the TRX ms and NTRC quadruple silencing plants (Fig.…”
Section: Impact Of Insufficient Content Of Trx Isoforms and Ntrc On Omentioning
confidence: 73%
“…Recent research suggested that cooperative control of chloroplast functions via the ferredoxin-thioredoxin reductase (FTR)/TRX and NTRC pathways is essential for plant viability. The mutual inactivation of the catalytic subunit of FTR (FTRb) and NTRC leads to the drastic loss of photosynthetic performance and causes a lethal phenotype (Yoshida and Hisabori, 2016). Last but not least, glutaredoxins utilize the reducing power of glutathione to catalyze disulfide reductions in the presence of NADPH and glutathione reductase and operate, like TRXs, as dithiol reductants (Meyer et al, 2012).…”
mentioning
confidence: 99%